Abraham Lincoln papers - Lincoln, Abraham, 1809-1865.; Lincoln, Abraham, 1809-1865.
Correspondence and other papers relating primarily to Abraham Lincoln's presidency and the Civil War. Includes two drafts of the Gettysburg address, material preserved by John G. Nicolay in his capacities as Lincoln's secretary and editor of the Complete Works of Abraham Lincoln (1905), a letter of condolence from Queen Victoria to Mary Todd Lincoln, and a small amount of material about Lincoln dated after 1865. Correspondents include Nathaniel Prentiss Banks, Edward Bates, Montgomery Blair, Benjamin Harris Brewster, Salmon P. Chase, Schuyler Colfax, David Davis, Ulysses S. Grant, John Hay, Andrew Johnson, Reverdy Johnson, George Brinton McClellan, George Gordon Meade, Edwin D. Morgan, John G. Nicolay, William S. Rosecrans, William Henry Seward, Horatio Seymour, Caleb B. Smith, James Speed, Edwin McMasters Stanton, Charles Sumner, Lyman Trumbull, Lew Wallace, E.B. Washburne, and Gideon Welles.
Series 1, General correspondence (1833-1916), available through the Library of Congress Web site.
Microfilm edition (J. F. Alexander) available
Microfilm edition of Series 1-3 available
Microfilm produced from originals in the Manuscript Division.
appropriate custodial divisions of the Library of Congress.
U.S. president and representative and lawyer from Illinois.
Keywords: Banks, Nathaniel Prentiss, -- 1816-1894 -- Correspondence; Bates, Edward, -- 1793-1869 -- Correspondence; Blair, Montgomery, -- 1813-1883 -- Correspondence; Brewster, Benjamin Harris, -- 1816-1888 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Davis, David, -- 1815-1886 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Johnson, Andrew, -- 1808-1875 -- Correspondence; Johnson, Reverdy, -- 1796-1876 -- Correspondence; Lincoln, Mary Todd, -- 1818-1882 -- Correspondence; McClellan, George Brinton, -- 1826-1885 -- Correspondence; Meade, George Gordon, -- 1815-1872 -- Correspondence; Morgan, Edwin D. -- 1811-1883 -- Correspondence; Nicolay, John G. -- 1832-1901.; Nicolay, John G. -- 1832-1901 -- Correspondence; Rosecrans, William S. -- 1819-1898 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Seymour, Horatio, -- 1810-1886 -- Correspondence; Smith, Caleb B. -- 1808-1864 -- Correspondence; Speed, James, -- 1812-1887 -- Correspondence; Stanton, Edwin McMasters, -- 1814-1869 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Trumbull, Lyman, -- 1813-1896 -- Correspondence; Victoria, -- Queen of Great Britain, -- 1819-1901 -- Correspondence; Wallace, Lew, -- 1827-1905 -- Correspondence; Washburne, E. B. -- 1816-1887 -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1861-1865.; Lawyers; Presidents -- United States; Representatives, U.S. Congress -- Illinois